Returns to Tilapia fish farming in Ghana: Implications for Tilapia pooled investment vehicles - Kwami Adanu; Mawufemor Adanu (The Journal of Entrepreneurial Finance (JEF), 2016)
In Ghana, the private sector's response to financing constraints associated with aquaculture investment has been to employ Pooled Investment Vehicles (PIVs). Unfortunately, several of these PIVs faced insolvency with huge losses to investors as returns promised investors turn out to be unrealizable. The premise of this study is that such insolvency problems occur mainly because of the lack of reliable data on likely returns and risk associated with Tilapia farm investments. This study improves on the 'single value' profitability estimates of previous studies by performing Value at Risk (VaR) analyses on estimated farm-level returns, and 5,000 Monte Carlo simulation trials of the NPV to examine distribution of the long term returns to Tilapia farms. Results indicate that 99 percent of farms surveyed recorded positive net returns with an average return of 36 percent per cycle or 72 percent per annum. The VaR result suggests that there is a 5 percent chance that short-term returns in Tilapia farming would fall below 20 percent level per 6-month cycle. Further, 80 percent of the farms included in the study recorded positive NPV. The simulation produced Average NPV of 4026 Ghana cedis and IRR of 24 percent per cycle. This implies that offering more than 48 percent returns per annum to investors results in negative NPVs that lead to insolvency.
Keywords: 650; Returns; Tilapia; Cage; Risk; Ghana